Abstracts of the Southern African Transplantation Society 2017 Congress (Durban, 1-3 September 2017) - Hariparshad, Sudesh (African Journal of Nephrology, 2017)
Abstracts of the Southern African Transplantation Society 2017 Congress held in Durban, 1-3 September 2017. Abstracts published as received.